Հանգիտությունը Գրիգոր Նարեկացու «Մատեան ողբերգութեան» երկի աշխարհաբար թարգմանություններում - Ապրեսյան, Անուշ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В поэтическом звучании «Книги скорбных песнопений» Григора Нарекаци особую роль играет консонанс – последовательное повторение одних и тех же или схожих звуков. Aвтор применял как обе формы консонанса – аллитерацию (повторение согласных звуков) и ассонанс (повторение гласных звуков), так и их новых и более сложных форм – сцепленного консонанса, чередования одинаковых или схожих звуков соседних слов. Поскольку в поэме Нарекаци консонанс является доминантой, то это должно было найти отражение и в переводах. Мы изучили явление консонанса в стихотворных переводах «Книги скорбных песнопений» на современный восточноармянский язык, выполненных Мкртычем Хераняном и Вазгеном Геворкяном. В переводе Мкртыча Хераняна формы консонанса в основном выражены тождественно, за исключением тех частей, где повторение букв получило значение повторения окончаний, или повторяющиеся элементы были заменены близкими или похожими звуками. Однако Вазген Геворкян иногда отходил от формы оригинала, поскольку она не давала возможности придать переводу необходимую поэтичность, а иногда и сохранить стихотворный размер. The sonority of the Book of Lamentation by Grigor Narekatsi was promoted by the consistent repetition of the same or similar sounds, i.e. consonance. In the Book of Lamentation the author used both forms of consonance: alliteration (repetition of consonants) and assonance (repetition of vowels), as well as their new and more complex forms, as concatenated consonance, alternation of the same or similar sounds of neighboring words. Since sound repetitions played an important role in Narekatsi’s work, it was necessary to represent them in the translations either. The present article studies the phenomena of consonance in the poetic translations of the Book of Lamentation into modern Eastern Armenian by Mkrtich Kheranyan and Vazgen Gevorkyan. In the translation by Mkrtich Kheranyan, the forms of consonance are basically identical, except for those parts where the repetition of letters coincides with the repetition of the endings, or the repeating elements are replaced with close or similar sounds. However, Vazgen Gevorkyan sometimes renounces the original form, since it does not allow to convey poetic sounding to the translation and keep the poetic metre. Hence, constraints of choosing words with different sound combinations.
Keywords: Բանասիրություն